Analisis Gaya Bahasa dalam Puisi Karya Siswa Kelas X SMA Negeri 1 Pangkep - Andi Nurfadillah Basri; Sulastriningsih Djumingin; Nurhusna (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This study aims to describe the form of language style in poetry by class X students of SMA Negeri 1 Pangkep. The research design used is descriptive qualitative. The data in this study are arrays or sentences containing stylistic language in poetry by students of class X SMA Negeri 1 Pangkep. The data collection technique was obtained using the reading and note-taking technique. Data analysis techniques are data analysis techniques according to Miles and Huberman, namely data reduction, data presentation, and conclusion drawing. The results showed that the most dominating language style was assonance. The meaning conveyed by students through the chosen language style. Some are expressed using the actual meaning (denotative) and some are expressed with additional meaning (connotative).